Optimal control over evolution stochastic systems and its application to stochastic models of financial mathematics - Biirdeinyi, A. G.; Svishchuk, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We consider problems of optimal stabilization of controlled evolution stochastic systems in semi-Markov media and their application to financial stochastic models.